Investigation of Formaldehyde Content in Dairy Products Available in Bangladesh by a Validated High Performance Liquid Chromatographic Method (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Highly nutritious dairy products are ingested regularly by all ages of population. Adulteration of dairy products to enhance the inherent stability and acceptability to common consumers by different harmful and toxic ingredients like formalin, an unpermitted preservative, has been a burning issue in Bangladesh over the last few years. The aim of this paper was to analyze the concentration of formaldehyde in dairy products most commonly sold in Bangladeshi markets by a validated reversed phase high performance liquid chromatographic (RP-HPLC) method to reveal the on-going alarming scenario in a scientific way. After pre-derivatization with 2,4- dinitrophenylhydrazine, formaldehyde was detected at 345 nm using a C18 column with acetonitrile and water (45:55) as mobile phase at a flow rate of 2.0ml/min. The validated method has been applied to 41 marketed dairy products, including pasteurized milk, UHT milk, banana- mango- and chocolate-milk, flavored yoghurt, lassi, buttermilk, and skimmed milk. However, no formaldehyde was detected among the tested dairy products.Dhaka Univ. J. Pharm. Sci. 15(2): 187-194, 2016 (December)